The Investments in Energy Distribution Networks: Does Company Ownership Matter? - Di Pillo, Francesca; Levialdi, Nathan; Marchegiani, Laura (International Journal of Energy Economics and Policy, 2020)
This paper revolves around the challenges currently tackled by the energy distribution sector, where infrastructural investments play a vital role in both increasing the industry's internal efficiency and developing national economies. In natural gas and electricity sectors, the liberalisation process began in Europe at the end of the 1990s has triggered a change in the industry's competitive framework, encouraging investments by companies aiming at improving their industrial and organisational efficiency. At the same time, liberalisation also brought about a change in the ownership of firms: private and mixed ownership companies are now actively participating in the market, together with state-owned enterprises. In the light of these significant changes, this study is aimed at establishing whether the companies' propensity to invest in infrastructures is connected with a specific form of ownership. So far, this specific topic has not been thoroughly investigated by empirical studies; this work tries to fill this gap by carrying out an empirical analysis on a sample of Italian energy distribution utilities operating in the natural gas and electricity sector. Keywords: infrastructure investments; energy distribution sector; private and public companies; mixed companies. JEL Classifications: L94, L95, L97, L98, Q48 DOI: https://doi.org/10.32479/ijeep.9511